Aprendizagem significativa sobre a dengue em espaços educativos - Shimada, Marly Satimi (2016)
The learning of science in educational becomes positive when students can make associations with their experienced reality, for better understanding and clarity in the formative aspect of science content. This research sought to use the Theory of Meaningful Learning and educational spaces having as theme dengue disease. It was emphasized mosquito Aedes aegypti characteristics, life cycle, breeding ground, as well as the symptoms, transmission, diagnosis, treatment and prevention of disease. The aim of this study was to analyze the possibility of meaningful learning in educational environments using dengue in the learning process. The students visited the institutionalized non-formal educational spaces, Laboratory of Malaria and Dengue and the Forest Science belonging to the National Institute for Research in the Amazon - INPA. This is a qualitative research, and the techniques used were observation, questionnaires and interviews. The study subjects were 33 students in a class of seventh year of morning shift of elementary school of a school of public network of Manaus. It was concluded that it was possible application of the Theory of Meaningful Learning in educational spaces, inside and outside the school environment sharpening the prior knowledge of the students who had the opportunity to learn beyond the classroom, expanding to different places and making new discoveries, expanding on practice the content presented. Given this, we can say that the students learned significantly in educational spaces using the dengue issue in the learning process.